Chapter 22: New nonprofit organization governance: driving impact by adopting a holistic governance view - Renz, Patrick (Edward Elgar Publishing, 2023)
Governance of nonprofit organizations (NPOs) is a concept that does not only explain the responsibilities of the top management level. It is also useful to understand and align the entire organization if the respective management concepts are consequently translated through all organizational levels. In fact, a more holistic governance view of the entire organization can leverage the organization in its impact orientation, effectiveness, and accountability. The chapter introduces the findings from assessments of 67 organizations and 700 persons on governance, middle management, and operational level. The chapter suggests a new governance understanding comprising themes such as system, mission, integrity, stakeholders, risks, and audit and reporting. This new NPO governance model requires to be implemented all through the organization in a level-adjusted bidirectional discourse. The research summarized in this chapter reveals that nearly all organizations have so-called governance gaps but they are mostly ignorant about them. This yields a substantial upward potential to improve the impact and sustainability of NPOs. The findings also suggest that further research develops a better understanding of the interplay between holistic governance and leadership.